Por uma poética cartográfica : estratégias para a construção da dramaturgia e da encenação em EntreNãoLugares - Rivera, Juliana Capilé (2021)
In the context of contemporary theater, dramaturgy is no longer a word linked only to the text; rather it has started to characterize the conjugations between differing elements of staging, such as body, voice, space and scenic objects. Dramaturgy can now be seen as part of staging, and uses a set of procedures in its elaboration, located in the instability of borderline junctions between territorialities, and in the stability of theatrical traditions. This dramaturgical construction conceived in the staging is defined by us, for this thesis, as a cartographic poetics. Our object is to probe these procedures in terms of the construction of the poetics of a theatrical performance, elaborated in accordance with the theatrical tradition of the Third Theater and laboratory theater, as disseminated by the Danish theater group Odin Teatret. We used, as a field of experience, the devising process of the show EntreNãoLugares (BetweenNoPlace), by Cia Pessoal de Teatro (MT) and Nordisk Teaterlaboratorium (DK), directed by Julia Varley (Odin Teatret). The making process employed cartography as a dramaturgical principle, a concept first elaborated by Deleuze and Guattari, and further developed by Rolnik, Passos and Kastrup. Methodologically, the thesis employs a literature review, self-descriptive analysis, and a case study, in addition to relying on artist notebooks. In order to understand dramaturgy as an expanded field, the role of mediation in theatrical work and questions regarding performativity, the writings of José Sánchez, Erika Fischer-Lichte and Eleonora Fabião are referred to, respectively. To better delineate the complexity of contemporary drama, authors such as Sílvia Fernandes, Patrícia Leonardelli, José da Costa and Stephen Baumgärtel are referenced. In terms of approaching laboratory theater and the Third Theater, we drew on the writing of Eugenio Barba, Jerzy Grotowski, Jane Turner and Patrick Campbell. We also used the testimonies of Odin Teatret actresses, such as Julia Varley, Roberta Carreri, Else-Marie Laukvik and Iben Nagel Rasmussen. What type of dramaturgy is elaborated in the Third Theater tradition? It is possible that this approach to dramaturgy is linked to the staging process, and the creation of the dramaturgy is the staging itself. The elaboration of the performance becomes a creative procedure that can appropriate methodologies such as cartography, thus realizing a cartographic poetics.